Queen & Slim [videorecording (DVD)] - Waithe, Lena, 1984-; Sevigny, Chloë; Flea (Musician); Woodbine, Bokeem; Kaluuya, Daniel, 1989- (Universal, 2020)
While on a forgettable first date together in Ohio, a black man and a black woman, are pulled over for a minor traffic infraction. The situation escalates, with sudden and tragic results, when the man kills the police officer in self-defense. Terrified and in fear for their lives, the man, a retail employee, and the woman, a criminal defense lawyer, are forced to go on the run. But the incident is captured on video and goes viral, and the couple unwittingly becomes a symbol of trauma.